IMPLEMENTASI NILAI KARAKTER TANGGUNG JAWAB DAN MANDIRI MELALUI PEMBELAJARAN TEMATIK MUATAN PPKN KELAS III SDN JANTEN KULON PROGO - Rifka Isfatiana; wachid pratomo; Chairiyah Chairiyah; Nadziroh Nadziroh (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2022)
In the current era, the progress of a nation is inseparable from character building. Because good character is very important to be owned by all students. This study aims to determine the implementation, supporting factors, constraints, and solutions in implementing the value of the character of responsibility and independence through thematic learning of the third grade Civics Education content at SDN Janten Kulon Progo. This research method uses descriptive qualitative data sources, namely the principal, third grade teacher, and third grade student. Data collection techniques are observation, interviews, and documentation. The analysis technique is by collecting data, reducing data, presenting data, and drawing conclusions. The results of this study indicate that (1) the teacher teaches the value of the character of responsibility and independence by giving direct examples in the context of daily life related to the value of these characters (2) There are still some students in grade III who have not formed an attitude of responsibility and independent, such as not collecting assignments on time, doing assignments from the teacher by cheating on their friends (3) Teachers and the school always provide examples of responsible and independent attitudes every time learning takes place (4) There are many supporting factors and obstacles faced in implementing values the character of responsibility and independence in third grade students of SD Negeri Janten Kulon Progo (5) There are several solutions to overcome obstacles in implementing the value of the character of responsibility and independence in grade III students of SD Negeri Janten Kulon Progo.